CD36- and GPR120-mediated Ca²⁺ signaling in human taste bud cells mediates differential responses to fatty acids and is altered in obese mice - Ozdener, Mehmet Hakan; Subramaniam, Selvakumar; Sundaresan, Sinju; Sery, Omar; Hashimoto, Toshihiro; Asakawa, Yoshinori; Besnard, Philippe; Abumrad, Nada A; Khan, Naim Akhtar (Gastroenterology, 2014)
BACKGROUND & AIMS: It is important to increase our understanding of gustatory detection of dietary fat and its contribution to fat preference. We studied the roles of the fat taste receptors CD36 and GPR120 and their interactions via Ca(2+) signaling in fungiform taste bud cells (TBC). METHODS: We measured Ca(2+) signaling in human TBC, transfected with small interfering RNAs against messenger RNAs encoding CD36 and GPR120 (or control small interfering RNAs). We also studied Ca(2+) signaling in TBC from CD36(-/-) mice and from wild-type lean and obese mice. Additional studies were conducted with mouse enteroendocrine cell line STC-1 that express GPR120 and stably transfected with human CD36. We measured release of serotonin and glucagon-like peptide-1 from human and mice TBC in response to CD36 and GPR120 activation. RESULTS: High concentrations of linoleic acid induced Ca(2+) signaling via CD36 and GPR120 in human and mice TBC, as well as in STC-1 cells, and low concentrations induced Ca(2+) signaling via only CD36. Incubation of human and mice fungiform TBC with lineoleic acid down-regulated CD36 and up-regulated GPR120 in membrane lipid rafts. Obese mice had decreased spontaneous preference for fat. Fungiform TBC from obese mice had reduced Ca(2+) and serotonin responses, but increased release of glucagon-like peptide-1, along with reduced levels of CD36 and increased levels of GPR120 in lipid rafts. CONCLUSIONS: CD36 and GPR120 have nonoverlapping roles in TBC signaling during orogustatory perception of dietary lipids; these are differentially regulated by obesity.
Keywords: membránové mikrodomény; obezita; chuťové pohárky; inositol-1,4,5-trisfosfát; Receptors, G-Protein-Coupled; chování zvířat; Humans; Taste Perception; Serotonin; serotonin; Food Preferences; Inositol 1,4,5-Trisphosphate; Diet, High-Fat; GLP-1; Taste Buds; chuť; Linoleic Acid; lidé; zvířata; Calcium Signaling; myši; preference v jídle; myši inbrední C57BL; kyselina linolová; Mice; buněčné linie; myši knockoutované; transfekce; chuťová percepce; Behavior, Animal; Cell Line; glukagonu podobný peptid 1; Mice, Knockout; Taste; Glucagon-Like Peptide 1; vápníková signalizace; Mice, Inbred C57BL; Lipids; RNA Interference; CD36 Antigens; Transfection; dieta s vysokým obsahem tuků; Obesity; Animals; receptory spřažené s G-proteiny; Membrane Microdomains; Disease Models, Animal; antigeny CD36; RNA interference; modely nemocí na zvířatech